Effects of Levetiracetam Compared to Valproate on Cognitive Functions of Patients with Epilepsy - El Sabaa RM (Dove Medical Press, 2020)
Ramy M El Sabaa,1 Emad Hamdi,2,3 Nermin Aly Hamdy,4 Hatem A Sarhan5 1Clinical Pharmacy Department, Faculty of Pharmacy, Deraya University, Minia, Egypt; 2Deraya University President, Minia, Egypt; 3Psychiatry Department, Faculty of Medicine, Cairo University, Cairo, Egypt; 4Neurology Department, Faculty of Medicine, Minia University, Minia, Egypt; 5Pharmaceutics Department, Faculty of Pharmacy, Minia University, Minia, EgyptCorrespondence: Ramy M El SabaaClinical Pharmacy Department, Faculty of Pharmacy, Deraya University, Minia, New Minia 61768, EgyptTel +20-10-0635-0788Email dr.ramypharma@gmail.comObjective: This study compared the effect of levetiracetam (LEV) as monotherapy to sodium valproate (VPA) as monotherapy on cognitive functions in patients with epilepsy.Methods: This was a comparative prospective study on 50 patients with newly diagnosed epilepsy started on antiseizure medications. Patients were selected from the neurology-outpatient clinics at Minia University Hospital, Minia, Egypt. They were divided into two groups: group treated with LEV and group treated with VPA. All patients were subjected to cognitive function assessment using reaction-time tests, trail-making tests, and Wisconsin card-sorting test before treatment and 3 months after treatment.Results: Both groups of patients showed reduction in seizure frequency. However, patients on LEV showed significant improvement in measured cognitive functions 3 months after starting treatment, while patients in the VPA group showed significant impairment in measured cognitive functions 3 months after starting treatment.Conclusion: Both groups of patients showed reduction in seizure frequency. However, patients on LEV showed significant improvement in measured cognitive functions 3 months after starting treatment, while patients in the VPA group showed significant impairment in measured cognitive functions 3 months after starting treatment.Keywords: cognitive function, epilepsy, levetiracetam, valproate, monotherapy